A new polymorph of metacetamol1. Issue 32 (28th August 2015) - McGregor, Lindsay; Rychkov, Denis A.; Coster, Paul L.; Day, Sarah; Drebushchak, Valeri A.; Achkasov, Andrei F.; Nichol, Gary S.; Pulham, Colin R.; Boldyreva, Elena V.
<x xml:space="preserve">Abstract</x> The existence of a new polymorph of metacetamol together with its properties are reported for the first time.